2022
DOI: 10.1155/2022/3127135
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Processing and Characterization of Novel Bio‐Waste Hybrid Brick Composites for Pollution Control

Abstract: The main focus of this research is to enhance the use of eco-friendly materials these days. The current materials used in building construction are chemical-based and are harmful to humans and the environment. This research work has developed a new type of hybrid brick by using natural fibres and waste materials. This research focuses on fabricating novel bricks reinforced with different percentages of coconut waste fibre, wheat straw fibre, waste wood animal dung ash, gypsum, sand, and cement. The fabricated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Figure 3(c) shows the sintering temperature and weight fraction of boron carbide with surface roughness. From Figure 3(c), it is revealed that the optimal surface roughness was highly attained at the medium level of sintering temperature and weight fraction at 8% B 4 C [30]. Therefore, this surface roughness was highly accumulated in the medium level weight fraction at 8% of boron carbide, low level of compaction pressure 300 MPa, and medium level of temperature 480 °C.…”
Section: Contour Plot Analysis Of Machining Responsesmentioning
confidence: 91%
“…Figure 3(c) shows the sintering temperature and weight fraction of boron carbide with surface roughness. From Figure 3(c), it is revealed that the optimal surface roughness was highly attained at the medium level of sintering temperature and weight fraction at 8% B 4 C [30]. Therefore, this surface roughness was highly accumulated in the medium level weight fraction at 8% of boron carbide, low level of compaction pressure 300 MPa, and medium level of temperature 480 °C.…”
Section: Contour Plot Analysis Of Machining Responsesmentioning
confidence: 91%
“…In particular, CNNs are popular for the automation of lung nodule detection, imaging classified pattern analysis, and estimation of cancer risk. Furthermore, machine learning-based transfer learning is used to adjust pre-trained CNNs to be applicable to the analysis of medical images and, therefore, develop a more stable and effective diagnosis system [15]- [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The addition of particles changes the other significant properties of the matrix, while fibre addition of fibres contributes primarily to the load‐bearing properties. The effectiveness of particle addition and its significant contribution to polymer matrix composites have been supported by more testimonials in recent decades (Mahalingam et al 2022 and Kumar et al 2022). Biopolymers, including cellulose, chitosan, chitin, and lignin, are notable biopolymers among ceramic and hard bioparticles that can strengthen the matrix material at the microscopic level and enhance its properties.…”
Section: Introductionmentioning
confidence: 95%